High-yield cellulase production by Trichoderma reesei ZU-02 on corn cob residue - Liming, X.; Xueliang, S.
Cellulase production using corn cob residue from xylose manufacture as substrate was carried out by Trichoderma reesei ZU-02. It was found that on the same cellulose basis, the cellulase activity and yield produced on corn cob residue were comparable with that on purified cellulose. Under batch process, the optimum concentration of substrate was 40 g/l and the optimum C/N ratio was 8.0. In 500 ml flasks, cellulase activity reached 5.25 IU/ml (213.4 IU/g cellulose)after seven days' cultivation. In a 30 m3 stirred fermenter for large scale production, cellulase and cellobiase activity were 5.48 IU/ml (222.8 IU/g cellulase)and 0.25 IU/ml (10.2 IU/ g cellulose), respectively, after four days' submerged fermentation. The produced cellulase could effectively hydrolyze the corn cob residue, and the yield of enzymatic hydrolysis reached 90.4
Keywords: CELLULASE; CELLOBIASE; SUBMERGED FERMENTATION; CORN COB RESIDUE; HYDROLYSIS